Features of using a scenario-purposive approach for modeling and controlling the technological complex of milk production - Dovzhenko, Yevgenia (My University, 2014)
On the example of the pasteurization department, we clearly see the relationship between the objectives, operations, resources, objects, etc. The purposive scenario is used for simulation modeling of the process of object functioning, for forecasting the development of the situations and for making decisions.
Keywords: виробництво молока; управління; моделювання; milk production; management; modeling; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка